Depositional environment of the Lower Cretaceous Muling Formation of the Laoheishan Basin (NE China): Implications from geochemical and petrological analyses. (February 2017) - Song, Yu; Bechtel, Achim; Sachsenhofer, Reinhard F.; Groß, Doris; Liu, Zhaojun; Meng, Qingtao
Highlights: Excellent source potential of coal and oil shale is due to high liptinite content. The coal is subbituminous in rank and was formed in a low-lying mire. Organic matter in oil shale is terrigenous, rich in waxy and resinous lipids. Floral assemblage was dominated by Pinaceae, Cupressaceae/Taxodiaceae and ferns. Abstract: The Laoheishan Basin located in northeastern China is filled with non-marine coal- and "oil shale" (oil-prone mudstone) sediments of the Lower Cretaceous Muling Formation. Based on petrological, mineralogical and geochemical methods, the depositional environment during organic matter (OM) accumulation is investigated for the first time. The coal is subbituminous in rank. Petrological and bulk geochemical data indicate sapropelic coal, deposited in low-lying mire under freshwater conditions. High pristane/phytane ratios provide evidence for a land plant origin of OM and oxic conditions during deposition. A neutral to slightly alkaline pH is reflected by the presence of carbonate. High liptinite contents and terpenoid biomarker composition indicate high amounts of resinous OM. During "oil shale" deposition, a raised water table was favorable for OM preservation under oxic to dysoxic conditions. The "oil shales" in the lower unit of the succession (not associated with coal) are characterized by high hydrogen index and resinite contents interpreted to reflect deposition at elevated water depths. In contrast to the findings of previous studies on "oil shales" in China indicating its origin from algal OM, a predominance of terrigenous OM, rich in waxy and resinous lipids, is implied from biomarker and maceral composition. The Lower Cretaceous "oil shale" and coal in the Laoheishan Basin contain high amounts of land plant derived terpenoid biomarkers, derived from Coniferales (e.g., Pinaceae, Cupressaceae/Taxodiaceae, Araucariaceae, Podocarpaceae) and ferns. The results are in agreement with palynological data. The data highlight the potential of resinous and waxy OM to form excellent hydrocarbon source rocks.